Sosialisasi Tinjauan Hukum Islam Dalam Jual Beli Online Bagi Masyarakat Desa Pulau Sembilan - Diyan Yusri; Alang Sidek; Indra Syahputra (peduli riset dan pengabdian masyarakat, 2023)
Pulau Sembilan is a village in the Pangkalan Susu sub-district, Langkat Regency, North Sumatra province, Indonesia. Although it is often regarded as an area that does not have popular tourist attractions, lately, a very interesting tourist spot in North Sumatra to be used as a recreational destination is Pulau Sembilan in Langkat. This enchanting island has a variety of things that are sure to attract the attention of many tourists to visit it. Even though it is not as popular as other island tourist attractions, its existence cannot be ignored. Recently, the level of popularity of Pulau Sembilan has been increasing. This community service activity discusses the meaning of online buying and selling, online buying and selling laws, online buying and selling requirements, types of online buying and selling products, online buying and selling transaction methods and buying and selling online in the view of Islamic law. The purpose of this community service activity is to provide an introduction to online buying and selling in a review of Islamic law to the people of Pulau Sembilan village, with the hope that the socialization participants can understand buying and selling online according to Islamic law and with this socialization participants can carry out correct transactions in buying and selling online so that they will improve the economy of the whole society